2003
DOI: 10.3201/eid0909.020654
|View full text |Cite
|
Sign up to set email alerts
|

Paecilomyces lilacinusVaginitis in an Immunocompetent Patient

Abstract: Paecilomyces lilacinus, an environmental mold found in soil and vegetation, rarely causes human infection. We report the first case of P. lilacinus isolated from a vaginal culture in a patient with vaginitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
0
19
0
2
Order By: Relevance
“…The incidence of infections in immunocompetent hosts is also increasing. [2] Paecilomyces lilacinus has been reported to cause cutaneous infections including catheter-related fungemia, sinusitis, [3] dermatitis, and disseminated disease secondary to application of a contaminated skin lotion in immunocompromised patients. [4] P. lilacinus and P. variotii are the two species most frequently associated with human disease.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of infections in immunocompetent hosts is also increasing. [2] Paecilomyces lilacinus has been reported to cause cutaneous infections including catheter-related fungemia, sinusitis, [3] dermatitis, and disseminated disease secondary to application of a contaminated skin lotion in immunocompromised patients. [4] P. lilacinus and P. variotii are the two species most frequently associated with human disease.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, certain fungi causing vaginitis also have been encountered in immunocompetent hosts. 6,7 Fruiting bodies are very important in identification of a particular fungus and its species, depending on the length and width of conidiophores, shape of vesicles and the chains of conidia. In the present case, all of the above factors strongly suggested that the fungus present in the Pap smear was a contaminant and the probable species was Aspergillus fumigatus.…”
Section: Discussionmentioning
confidence: 99%
“…This species can colonize materials such as catheters and plastic implants and can contaminate antiseptic creams and lotions, causing infections in immunocompetent and immunocompromised patients (Castro et al ., 1990; Orth et al ., 1996; Itin et al ., 1998). The prevalence of P. lilacinus in patients has increased recently (Carey et al ., 2003; Rosmaninho et al ., 2010). A review of 119 infections caused by P. lilacinus after 1964 showed that the most frequent manifestation is keratitis, but other sites of the body were also affected (Pastor & Guarro, 2006).…”
Section: Introductionmentioning
confidence: 99%